2017
DOI: 10.1155/2017/8325040
|View full text |Cite
|
Sign up to set email alerts
|

Off‐Design Behavior Analysis and Operating Curve Design of Marine Intercooled Gas Turbine

Abstract: The intercooled gas turbine obtained by adopting an indirect heat exchanger into an existing gas turbine is one of the candidates for developing high-power marine power units. To simplify such a strong coupled nonlinear system reasonably, the feasibility and availability of qualifying equivalent effectiveness as the only parameter to evaluate the intercooler behavior are investigated. Regarding equivalent effectiveness as an additional degree of freedom, the steady state model of a marine intercooled gas turbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…This simplification will surely bring some differences in comparison to the case when the combustion gases were used, but the differences will be small because the combustion gases from the main gas turbine as well as combustion gases from the additional combustion chamber, Fig. 1, are dominantly composed of air with a small proportion of fuel [33,34]. Therefore, this simplification will not have a major influence on the obtained exergy analysis results for any component as well as for the whole observed system, and at the same time will make performed calculations easier and faster.…”
Section: Introductionmentioning
confidence: 99%
“…This simplification will surely bring some differences in comparison to the case when the combustion gases were used, but the differences will be small because the combustion gases from the main gas turbine as well as combustion gases from the additional combustion chamber, Fig. 1, are dominantly composed of air with a small proportion of fuel [33,34]. Therefore, this simplification will not have a major influence on the obtained exergy analysis results for any component as well as for the whole observed system, and at the same time will make performed calculations easier and faster.…”
Section: Introductionmentioning
confidence: 99%
“…Referencing to the design features of intercooled system for LMS100 ( Figure 1) and WR-21 ( Figure 2), a large number of investigations have been carried out in the past decades to study the operating characteristics of intercooled system and its effect on gas turbine. [5][6][7][8] All of the available results indicated that the heat exchange condition of intercooled system can directly affect the stable and dynamic performances of gas turbine. Besides, a careful inspection of Figures 1 and 2 reveals that although the intercooled systems used in LMS100 and WR-21 are significantly different, the corresponding heat exchange between compressed air and coolant is usually wasted directly.…”
Section: Introductionmentioning
confidence: 99%
“…This is considered one of the main methods by which develop high-power marine power units. Ji et al [ 27 ] presented an analysis of a simplified coupled nonlinear system, see Figure 19 , and developed a new model for the steady-state of a marine intercooled gas turbine that can be used for simulating off-design performance.…”
Section: Gas Turbine Power Plant Equipment Performance and Improvementsmentioning
confidence: 99%
“…The operating diagram of the intercooled gas turbine was optimized using a three-dimensional graphical method. The resulting operating curves revealed that the control strategy at steady-state conditions for the intercooled gas turbine should be variable cycle control [ 27 ].…”
Section: Gas Turbine Power Plant Equipment Performance and Improvementsmentioning
confidence: 99%